2019
DOI: 10.1080/03054985.2019.1645651
|View full text |Cite
|
Sign up to set email alerts
|

Trainee teachers’ knowledge of autism: implications for understanding and inclusive practice

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 44 publications
3
17
0
5
Order By: Relevance
“…Overall, in this review we found a lack of knowledge in most of the articles reviewed coinciding with prior reviews [61,62] and other studies [45]. We found that most of the articles revealed low [64,66,68,71,75,76,79,[84][85][86]95] or medium [65,67,73,74,77,78,80,82,91] levels of knowledge about ASD among their participants, coinciding with prior studies [21,25,36,37]. Indeed, most of the studies showed misconceptions [75,85,91] and gaps, or a lack of knowledge [71,77,85,95].…”
Section: Teachers' Knowledge Of Asd and Moderators That Possibly Influence Asdsupporting
confidence: 71%
See 2 more Smart Citations
“…Overall, in this review we found a lack of knowledge in most of the articles reviewed coinciding with prior reviews [61,62] and other studies [45]. We found that most of the articles revealed low [64,66,68,71,75,76,79,[84][85][86]95] or medium [65,67,73,74,77,78,80,82,91] levels of knowledge about ASD among their participants, coinciding with prior studies [21,25,36,37]. Indeed, most of the studies showed misconceptions [75,85,91] and gaps, or a lack of knowledge [71,77,85,95].…”
Section: Teachers' Knowledge Of Asd and Moderators That Possibly Influence Asdsupporting
confidence: 71%
“…In the case of studies with a pre-and post-test, we wrote down the first test result; in the other two situations, we calculated the average among article results. Eleven studies [64,66,68,71,75,76,79,[84][85][86]95] revealed low levels of knowledge regarding ASD among their participants; nine studies [65,67,73,74,77,78,80,82,91] reported medium knowledge, and five studies [65,87,89,90,92] described a high level of knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, teachers still have difficulty operationalising these concepts, and including learners with additional needs. There are issues with attitudes to inclusion and disability [ 7 ], understanding of specific needs, for example autism and other neurodevelopmental disorders [ 8 ], and level of knowledge of staff [ 9 ], leading to ongoing calls for more training, support, and resources [ 10 ]. Attempting to reduce unequal outcomes for all children is the primary goal [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two variables that may relate to attitudes are knowledge and experience. With greater knowledge, educators may, for example, better understand an autistic child's ways of communicating, and have a greater appreciation of sensory sensitivities (Barnhill, 2016;Vincent & Ralston, 2020). Segall & Campbell (2012) surveyed 196 educational professionals in the USA and found many did not know the answers to knowledge questions and had not heard of different support strategies for autistic pupils.…”
Section: Introductionmentioning
confidence: 99%